Análise da Sobrevivência e Desenvolvimento de Mudas de Pau-Rosa (Aniba rosaeodora Ducke) em Clareiras Artificiais - Fonseca, Gisele Cândida Freitas da (2007)
In different sizes of artificial gaps, located at Estação Experimental de Silvicultura Tropical (EEST-INPA), in Manaus - AM, survival, development, herbivory susceptibility related to density and the nutritional estate of rose-wood plants (Aniba rosaeodora Ducke) were analyzed after three years of its establishment. The experiment was realized in three different size gaps (little gap, median gap and big gap), and a control-area under closed tree top was used to compare the influence of different luminosity incidence on plant growth. The gaps and the control-area are the different treatments. The data taken was: survival, by counting the number of plants, stem height, diameter, estimated herbivory percentage to calculate the herbivory index and determination of the nutritional state by chemical laboratorial analysis of material leaves. These data were taken in March and November of the year 2005, and analyzed by ANOVA and Tukey (5% significance) tests. Better plant development was observed in a bigger gap. It was not observed differences of survival between the treatments. There were no evidences of herbivory related to density. It was observed nutritional deficit in all treatments.